Ethnic disparity in altruism towards reforestation: A social preference experiment in Mindoro, Philippines - Imelda Revilla Molina; Katelyn Castillo; Klarizze Anne Martin Puzon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper presents a framed field experiment on ecological altruism in Mindoro, Philippines. Behavioural differences between ethnic groups in Mindoro-the Tagalogs and the Mangyans-were investigated. We designed a two-part donation task (i.e. dictator game) where the recipient of the donation was a local reforestation project. There were two treatments: participants played either the giving game (GG) or the taking game (TG). In the first part (GG), respondents were asked how much they will donate towards reforestation; in the second part (TG), respondents were asked how much money they will take away from the project and keep for themselves. The second part was the same as the first, but participants were asked what they will do if a hypothetical partner, who was either the same or different ethnicity, donated half of the initial endowment to reforestation. Results indicate that Mangyans, who are predominantly farmers, tend to give more in the TG than the GG. Tagalog respondents were not sensitive to framing. Finally, other-ethnicity dynamics did not have a strong effect.
Keywords: C90; Q23; Q56; Q57; 330; framed field experiment; reforestation; dictator game; framing